Participatory implementation science to increase the impact of evidence-based cancer prevention and control - Ramanadhan, Shoba; Davis, Melinda M.; Armstrong, Rebecca; Baquero, Barbara; Ko, Linda K.; Leng, Jennifer C.; Salloum, Ramzi G.; Vaughn, Nicole A.; Brownson, Ross C. (Cancer causes & control, 2018)
It is critical to accelerate the integration of evidence-based programs, practices, and strategies for cancer prevention and control into clinical, community, and public health settings. While it is clear that effective translation of existing knowledge into practice can reduce cancer burden, it is less clear how best to achieve this. This gap is addressed by the rapidly growing field of implementation science. Given that context influences and is influenced by implementation efforts, engaging stakeholders in the co-production of knowledge and solutions offers an opportunity to increase the likelihood that implementation efforts are useful, scalable, and sustainable in real-world settings. We argue that a participatory implementation science approach is critical, as it supports iterative, ongoing engagement between stakeholders and researchers to improve the pathway between research and practice, create system change, and address health disparities and health equity. This article highlights the utility of participatory implementation science for cancer prevention and control research and addresses (a) the spectrum of participatory research approaches that may be of use, (b) benefits of participatory implementation science, and (c) key considerations for researchers embarking on such projects.